2012
DOI: 10.4103/2230-8210.95661
|View full text |Cite
|
Sign up to set email alerts
|

Teriparatide - Indications beyond osteoporosis

Abstract: Osteoporosis is a condition of impaired bone strength that results in an increased risk of fracture. The current and most popular pharmacological options for the treatment of osteoporosis include antiresorptive therapy, in particular, oral bisphosphonates (alendronate, risedronate, ibandronate). Anabolic agents like teriparatide have widened our therapeutic options. They act by directly stimulating bone formation and improving bone mass quantity and quality. Two forms of recombinant human parathyroid hormone (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 54 publications
0
12
0
1
Order By: Relevance
“…[ 1 4 ] Apart from being used in osteoporotic individuals, insights into its action on many other conditions are unraveling. [ 6 ] Animal studies yielded promising results for teriparatide usage to enhance postero-lateral fusion mass in rat models. [ 13 ] In human studies relating to teriparatide, most authors studied its effect only in osteoporotic individuals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 1 4 ] Apart from being used in osteoporotic individuals, insights into its action on many other conditions are unraveling. [ 6 ] Animal studies yielded promising results for teriparatide usage to enhance postero-lateral fusion mass in rat models. [ 13 ] In human studies relating to teriparatide, most authors studied its effect only in osteoporotic individuals.…”
Section: Discussionmentioning
confidence: 99%
“…[ 5 ] Since its availability in market, indications are unravelling and is being attempted in many conditions including fracture healing, dental stability, hypoparathyroidism, and hypocalcaemia. [ 6 , 7 ] Another evolving field of interest is the role of teriparatide for enhancing bone graft union and osseo-integration of implants. [ 8 , 9 ] It is said to accelerate bone graft union and reduce the incidence of pedicle screw loosening after lumbar spinal fusion surgeries.…”
Section: Introductionmentioning
confidence: 99%
“…Teriparatide, an anabolic agent, is a recombinant form of PTH given intermittently to increase number and activity of osteoblasts, ultimately improving bone mass and skeletal architecture 7 . In contrast to bisphosphonates, which lower inflammatory cytokine production, studies have found that PTH increases IL-1 and IL-6 production and acts synergistically with IL-1 to promote bone resorption 8, 9.…”
Section: Discussionmentioning
confidence: 99%
“…Teriparatid ist aktuell für die Osteoporosetherapie für eine maximale Dauer von 24 Monaten zugelassen. Der Einsatz bei AFF zur Verbesserung der Frakturheilung zählt demnach aktuell als Off-Label-Use [31].…”
Section: Merkeunclassified